1993
DOI: 10.1080/02701367.1993.10607594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traditional and Reversed Bandwidth Knowledge of Results on Motor Learning

Abstract: The effects of two types of bandwidth (BW) knowledge of results (KR) were investigated on the acquisition and immediate retention of a timing task. Traditional and reversed BW KR groups were compared with two yoked control groups. Forty-eight randomly assigned subjects completed 60 acquisition trials and 20 no-KR retention trials. Acquisition analysis indicated a greater timing accuracy for the traditional BW group in comparison to the reversed BW group. During retention, less absolute constant error was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…The modified-bandwidth condition had significantly more error on retention than did the bandwidth condition, with the performances of the yoked and lOO%-KR conditions being between the other two conditions. These results are consistent with those of other studies that have shown some form of a learning benefit for the bandwidth-KR method (Cauraugh et al, 1993;Lee & Carnahan, 1990;Lee & Maraj, 1994;Sherwood, 1988). Lee and Carnahan considered whether the benefit of bandwidth KR was caused by the reduced relative frequency of KR, which occurs with the bandwidth method.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The modified-bandwidth condition had significantly more error on retention than did the bandwidth condition, with the performances of the yoked and lOO%-KR conditions being between the other two conditions. These results are consistent with those of other studies that have shown some form of a learning benefit for the bandwidth-KR method (Cauraugh et al, 1993;Lee & Carnahan, 1990;Lee & Maraj, 1994;Sherwood, 1988). Lee and Carnahan considered whether the benefit of bandwidth KR was caused by the reduced relative frequency of KR, which occurs with the bandwidth method.…”
Section: Discussionsupporting
confidence: 93%
“…The use of a bandwidth, or area of tolerance, to determine when KR is to be presented is an effective method to enhance motor skill acquisition (Cauraugh et al, 1993;Lee & Carnahan, 1990;Lee & Maraj, 1994). The benefit of the bandwidth method may be attributable to the fact that KR presentation is based on the performance of the learner.…”
Section: Discussionmentioning
confidence: 98%
“…Together with the earlier work on the same topic (Cauraugh et al, 1993;Gordon & Gottlieb, 1967;Williams & Briggs, 1962), it is now established that for effective learning of tracking skills, the onset of a stimulus should be associated with erroneous performance, not with correct performance. Our results also suggest that lane departure warning systems that become increasingly available in real vehicles may have a benefit for learning.…”
Section: Discussionmentioning
confidence: 97%
“…Experimental studies of the bandwidth KR effect reveal that learning is enhanced when a relatively wide range of error tolerance is used, compared to a relatively narrow range of tolerance! (Annett, 1959;Cauraugh, Chen, & RadIo, 1993;Lee, White, & Carnahan, 1990;Reeve, Dornier, & Weeks, 1990;Sherwood, 1988).…”
mentioning
confidence: 98%